NOWADAYS CORPORATE STRATEGY: BUSINESS MODEL CANVAS AND SWOT AS A FOUNDATION - Rahmawati, Sisca Dian; Putra, Febrianur Ibnu Fitroh Sukono; Panjaitan, Roymon; Budiantoro, Risanda Alirastra; Lamidi, Lamidi (Universitas Dian Nuswantoro, 2024)
The purpose of this study is to determine the development of business strategy with a business model canvas approach and to determine SWOT analysis at company X. This study uses a qualitative research method using the Business Model Canvas (BMC) as a guide to identify business models and then uses SWOT for each metrics. Based on the SWOT analysis that has been produced, there are several business strategies that need to be carried out by PT. X, including producing high enough products, developing target markets, carrying out product development, selling outlet products, e-commerce, and various social media, conducting development of new innovations for products and many more.